2015
DOI: 10.1039/c4ob02632b
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the active site of β4GalT7: modifications of the aglycon of aromatic xylosides

Abstract: Proteoglycans (PGs) are macromolecules that consist of long linear polysaccharides, glycosaminoglycan (GAG) chains, covalently attached to a core protein by the carbohydrate xylose. The biosynthesis of GAG chains is initiated by xylosylation of the core protein followed by galactosylation by the galactosyltransferase β4GalT7. Some β-d-xylosides, such as 2-naphthyl β-d-xylopyranoside, can induce GAG synthesis by serving as acceptor substrates for β4GalT7 and by that also compete with the GAG synthesis on core p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
1
40
1
Order By: Relevance
“…The product was isolated as a white solid via silica gel flash column chromatography (15:1 EtOAc/MeOH, 1% Et 3 N) in 59% yield (252 mg). The spectra match previously published data (Siegbahn et al, 2015). …”
Section: Methodssupporting
confidence: 88%
“…The product was isolated as a white solid via silica gel flash column chromatography (15:1 EtOAc/MeOH, 1% Et 3 N) in 59% yield (252 mg). The spectra match previously published data (Siegbahn et al, 2015). …”
Section: Methodssupporting
confidence: 88%
“…Remarkably, the authors propose that the l ‐xylo‐derivative 6 shows a much higher antithrombotic activity compared to the d ‐xylo‐enantiomer 5 and that only the compound with l ‐xylo conformation functioned as substrate for β4GalT7 when assayed with enzyme extracts from chicken embryo. This is in stark contrast to other investigations where l ‐enantiomers of xylosides rarely act as substrates for β4GalT7 …”
Section: Introductioncontrasting
confidence: 90%
“…For the measurement of the kinetic parameters for the galactosylation by β4GalT7, we used a slightly improved version of our previously published assay, which is reflected in that the kinetic parameters for the compounds analyzed might differ slightly from previous investigations (Table ) . For example, the K m value for the β‐ d ‐xyloside 7 was similar to previously reported values, whereas V max , k cat , and k cat / K m differed significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we showed that three tyrosine residues represent key structural elements of the acceptor active site likely creating a hydrophobic environment for the aglycone moiety of exogenous xylosides . Altogether, our results indicate that the mono‐xyloside 3d is taken up by β4GalT7 as efficiently as 4‐MUX, though with different kinetic behavior, whereas the second xylose moiety present in the xylobioside 4d molecule does not accommodate the hydrophobic environment of the enzyme active site …”
Section: Resultsmentioning
confidence: 79%